Configurations of the Individual in Modern Chinese Literature - Wang, Qin. author. aut Link
XI, 300 p. 1 illus.
Keywords: This book aims to demonstrate the multiplicity of configurations of the individual in modern Chinese literature through analyzing several classic texts written by Zhou Zuoren, Lu Xun, Lao She, and Mu Shiying. It attempts to refresh our understanding of the history of modern Chinese literature and indirectly responds to the controversial issue of “individual rights” (or “human rights”) in present-day China, showing that in modern Chinese literature, various configurations of the individual imply political possibilities that are not only irreconcilable with each other, but irreducible to the determination of the modern discourse of “individualism” introduced by the West. A groundbreaking work, it will give valuable context to political scientists and other scholars seeking to understand what "China" means in the 21st century. Qin Wang received his Ph.D. in Comparative Literature from New York University, USA. He is the translator of the Chinese editions of Jacques Derrida’s Donner la mort and La bête et le souverain, Volume 1, Richard Bernstein’s Radical Evil, Jacques Lezra’s Wild Materialism, and David Harvey’s A Brief History of Neoliberalism.